Motyw „próby” jako element procesu wychowywania w tekstach Pięcioksięgu - Lemański, Janusz (Verbum Vitae, 2012)
The notion of “trial” as an element of the bringing up of Israel. In this article we have tried to prove the thesis that the notion of “trial” derives from Deuteronomy. The “trial” was then combined with another metaphoric motive which depicted the relationship between JHWH and Israel as the relationship between father and son. From the canonic point of view, Israel did not stand up to the trial. Postexilic theology chose Abraham to be a positive example of going through the trial as he represents hope for the future.